Social interactions in international forums: a new model - Genovesi, Marco (2021)
This dissertation argues that the creation of a theoretical model able systematically to distinguish and categorize the different types of statements made during international forums can help answering certain fundamental questions related to the functioning of inter-state negotiations; and that this would lead to a greater understanding of international relations in general. The existing literature has not yet been able to build such a systematic process of categorization, and the main reason for this is that they attempted to distinguish different types of forum statements by looking at indiscernible objects: the true dispositions of forum participants. Trying to build and to initially test such a systematic, valid and reliable method of classification of forum statements, able to lead to the formulation of empirically testable hypotheses, is the objective of this research. This with the objective of providing to future research the tools to analyse international forums on sounder conceptual and methodological bases. The theoretical model in this dissertation presents a reviewed version of Jennifer Mitzen’s theory of collective intention, and it argues that forum types of statement can be distinguished on the basis of the intention they address. It is argued that forum types of statement can be classified in collectivist, particularistic and procedural ones. Furthermore, it is argued that greater frequency of collectivist statements in international forums is likely to be correlated with a greater legitimacy of the forums’ outputs. To test the plausibility of this hypothesis, two most-similar cases are compared through the lens of qualitative content analysis: the two Antarctic meetings which respectively led to the elaboration of CRAMRA and of the Madrid Protocol.